Dexmedetomidine for delirium prevention in adult patients following cardiac surgery: a meta-analysis of randomized controlled trials - Chang Meng; Duo Wang; Yue Zhao; Jing Sun; Guobin Miao; Lijuan Chen; Ying Bai; Peng Liu (Journal of Cardiothoracic Surgery)
Abstract Objectives To determine whether perioperative administration of dexmedetomidine reduces the incidence of postoperative delirium in adult patients undergoing cardiac surgery. Methods We searched the PubMed, Embase and Cochrane Library databases for randomized controlled trials from the last 10 years up to March 10, 2024. We then conducted a meta-analysis to evaluate the effectiveness and safety of dexmedetomidine in preventing delirium after cardiac surgery in adults. This meta-analysis followed the steps in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA2020) guidelines. This study is registered with INPLASY under number INPLASY202430132. Results A total of 2689 patients were included in our analyses. All included studies were randomized controlled trials. Dexmedetomidine can reduce the occurrence of delirium in patients after cardiac surgery(OR 0.75, 95%CI 0.57–0.98, I2 = 12%, P = 0.04). In terms of other end events, length of intensive care unit(ICU) stay(MD -0.16, 95%CI -1.85-1.53, I2 = 0%, P = 0.85) and mortality(OR 1.59, 95%CI 0.74–3.42, I2 = 0%, P = 0.23) were not statistically different with dexmedetomidine compared with placebo. Bradycardia (OR 0.85, 95%CI 0.54 ~ 1.34, I2 = 72%, P = 0.49) and hypotension (OR 1.97, 95%CI 0.96 ~ 4.03, I2 = 84%, P = 0.06) were not significantly different between the two groups. Conclusions Dexmedetomidine is safe for cardiac surgery patients and to some extent reduces the incidence of delirium in cardiac surgery patients, which is more important in preoperative use.